Continuous theta burst stimulation over left and right supramarginal gyri demonstrates their involvement in auditory feedback control of vocal production. (17th February 2022) - Li, Tingni; Zhu, Xiaoxia; Wu, Xiuqin; Gong, Yulai; Jones, Jeffery A; Liu, Peng; Chang, Yichen; Yan, Nan; Chen, Xi; Liu, Hanjun
Abstract: The supramarginal gyrus (SMG) has been implicated in auditory-motor integration for vocal production. However, whether the SMG is bilaterally or unilaterally involved in auditory feedback control of vocal production in a causal manner remains unclear. The present event-related potential (ERP) study investigated the causal roles of the left and right SMG to auditory-vocal integration using neuronavigated continuous theta burst stimulation (c-TBS). Twenty-four young adults produced sustained vowel phonations and heard their voice unexpectedly pitch-shifted by ±200 cents after receiving active or sham c-TBS over the left or right SMG. As compared to sham stimulation, c-TBS over the left or right SMG led to significantly smaller vocal compensations for pitch perturbations that were accompanied by smaller cortical P2 responses. Moreover, no significant differences were found in the vocal and ERP responses when comparing active c-TBS over the left vs. right SMG. These findings provide neurobehavioral evidence for a causal influence of both the left and right SMG on auditory feedback control of vocal production. Decreased vocal compensations paralleled by reduced P2 responses following c-TBS over the bilateral SMG support their roles for auditory-motor transformation in a bottom-up manner: receiving auditory feedback information and mediating vocal compensations for feedback errors.